Behavioural change and alcohol-fuelled violence: A field experiment - Iain W. Long; Kent Matthews; Vaseekaran Sivarajasingam (Cardiff University, Cardiff Business School, 2019)
We conduct a field experiment to assess whether alcohol-induced behavioural changes explain participants' recent history of violence. We find that being in a drinking environment, rather than intoxication, reduces participants' cognitive ability but increases their overconfidence. Those who experience small reductions in ability or become much more overconfident tended to have been involved in more violent incidents. Since these behavioural changes were largely unanticipated, our results suggest that individuals underestimate their true likelihood of becoming involved in violence when making alcohol consumption decisions. This presents additional challenges when formulating policy designed to deter alcohol-fuelled violence.
Keywords: C93; D91; I18; 330; Intoxication; over-optimism; violence